2009
DOI: 10.1093/aje/kwp131
|View full text |Cite
|
Sign up to set email alerts
|

Placental Vascular Pathology Findings and Pathways to Preterm Delivery

Abstract: The authors examined the associations between placental vascular findings and preterm delivery in 1,053 subcohort women (239 preterm, 814 term) from a Michigan pregnancy cohort study (1998-2004). Twenty-nine placental vascular variables from microscopic examinations were grouped into 5 constructs: 3 maternal constructs-obstructive lesions (MV-O), bleeding/vessel integrity (MV-I), and lack of physiologic conversion of maternal spiral arteries (MV-D)--and 2 fetal constructs--obstructive lesions (FV-O) and bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 34 publications
4
52
0
6
Order By: Relevance
“…Other complications include venous insufficiency, diagnosed using Laser Doppler or Ultrasonography, lumbar lordosis, identified using X-ray, and cramps, seen in Electromyography (Kaaja, 2009;Kelly et al, 2009). Maternal fever can result in intra-uterine hyperthermia and/or inflammation effects on the fetal brain, which may result on premature labor or ultimate fetal death (Laburn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other complications include venous insufficiency, diagnosed using Laser Doppler or Ultrasonography, lumbar lordosis, identified using X-ray, and cramps, seen in Electromyography (Kaaja, 2009;Kelly et al, 2009). Maternal fever can result in intra-uterine hyperthermia and/or inflammation effects on the fetal brain, which may result on premature labor or ultimate fetal death (Laburn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Also, an in vitro study demonstrated that Hcy enhanced the rate of spontaneous contraction of myometrium isolated from human pregnant uterus. [6,9,17] The current study showed that serum Hcy level is a supportive biomarker for prediction of preterm birth. However, there are no available persuasive findings derived from larger studies for comparison because Hcy has not been extensively evaluated in biomarker trials of complicated pregnancies other than preeclampsia.…”
Section: Discussionmentioning
confidence: 53%
“…This supports the possibility of vasculopathy role in initiation of preterm labor. [6] The current study was designed to investigate the uterine artery Doppler and the maternal serum Hcy concentrations as indirect predictors of sPTD among pregnant women hospitalized with threatened preterm labor.…”
Section: Introductionmentioning
confidence: 99%
“…С нарушени-ем ремоделирования спиральных артерий связано и раз-витие диагностированных нами в плацентах родильниц 1-й группы хронических геморрагических инфарктов с центральной локализацией и суммарной площадью более 33%. Наряду с расстройствами материнского кровообра-щения, ЗРП при ХАГ с присоединившейся ПЭ была свя-зана с виллузитом промежуточных и терминальных вор-син и с последующей гиповаскуляризацией их стромы, поскольку гестационная перестройка сосудистого компо-нента терминальных отделов ворсинчатого дерева, начи-ная с 27-й недели гестации, играет важную роль в обеспе-чении прироста массы плода [16][17][18]. С неполноценной сосудистой перестройкой в ворсинчатом хорионе, воспа-лением и низким гестационным сроком плацент связано и недоразвитие в них компенсаторных процессов в группе пациенток с ЗРП, что в сочетании с хроническими гемор-рагическими инфарктами и нарушением дифференци-ровки сосудисто-стромального компонента ворсин со-ставляет структурную основу хронической плацентарной недостаточности при ЗРП у женщин с ХАГ и присоеди-нившейся ПЭ.…”
Section: Discussionunclassified